Magnetotransport properties of iron microwires fabricated by focused electron beam induced autocatalytic growth - Porrati, F.; Sachser, R.; Walz, Marie-Madeleine; Vollnhals, Florian; Steinrück, Hans-Peter; Marbach, Hubertus; Huth, M. (Journal of Physics D-Applied Physics, 2011)
We have prepared iron microwires in a combination of focused electron beam induced deposition and autocatalytic growth from the iron pentacarbonyl, Fe(CO), precursor gas under ultra-high vacuum conditions. The electrical transport properties of the microwires were investigated and it was found that the temperature dependence of the longitudinal resistivity (ρ) shows a typical metallic behaviour with a room temperature value of about 88 νΩ cm. In order to investigate the magnetotransport properties we have measured the isothermal Hall-resistivities in the range between 4.2 and 260 K. From these measurements, positive values for the ordinary and the anomalous Hall coefficients were derived. The relation between anomalous Hall resistivity (ρ) and longitudinal resistivity is quadratic, , revealing an intrinsic origin of the anomalous Hall effect. Finally, at low temperature in the transversal geometry a negative magnetoresistance of about 0.2% was measured. © 2011 IOP Publishing Ltd.